Therapeutic implications of current Janus kinase inhibitors as anti-COVID agents: A review - Jain, Nem Kumar; Tailang, Mukul; Jain, Hemant Kumar; Chandrasekaran, Balakumar; Sahoo, Biswa Mohan; Subramanian, Anandhalakshmi; Thangavel, Neelaveni; Aldahish, Afaf; Chidambaram, Kumarappan; Alagusundaram, M.; Kumar, Santosh; Selvam, Palani (Frontiers in Pharmacology, 2023)
The enhanced understanding of the importance of cytokine signaling and associated downstream JAK-STAT signaling in multiple disease conditions has led to the emergence of JAK inhibitors (Jakinibs) as the promising treatment for a variety of autoimmune and inflammatory conditions related to skeletal, digestive, and integumentary systems. COVID-19 is the latest area of application for jakinib as the standalone novel immunomodulatory agent for treating critical cases of COVID-19. Among Jakinibs, Baricitinib is the first jakinib to join the COVID-19 therapeutic arsenal. Recently, FDA has approved baricitinib as the first immunomodulatory drug to treat hospitalized COVID-19 adult patients requiring supplemental oxygen, non-invasive or invasive mechanical ventilation, or ECMO. Several other Jakinibs are under investigation in multiple clinical trials for COVID-19, either as monotherapy or combined with other immunomodulatory agents. This review aimed to describe the progress in understanding JAK-STAT pathway signaling in the pathogenesis of COVID-19. Due to their dual anti-viral and anti-inflammatory potential, various reports have indicated the suitability of Jakinibs to be repurposed for COVID-19 infection. The current update on the clinical development of Jakinibs in the COVID-19 setting is also discussed in the present review. The exact molecular mechanism of Jakinibs in managing COVID-19 is mainly speculative; further research is warranted in this direction. Furthermore, the current review highlights the scintillating year of success for the Jakinibs as a pharmaceutical class, adding a number of new areas of applications in its therapeutic armamentarium. Twelve Jakinibs have been approved by different regulatory bodies for almost thirteen inflammatory and autoimmune disorders.